2002
DOI: 10.3390/i3040407
|View full text |Cite
|
Sign up to set email alerts
|

The O-H Bond Dissociation Energies of Substituted Phenols and Proton Affinities of Substituted Phenoxide Ions: A DFT Study

Abstract: Abstract:The accurate O-H bond dissociation enthalpies for a series of meta and para substituted phenols (X-C 6 H 4 -OH, X=H, F, Cl, CH 3 , OCH 3 , OH, NH 2 , CF 3 , CN, and NO 2 ) have been calculated by using the (RO)B3LYP procedure with 6-311G(d,p) and 6-311++G(2df,2p) basis sets. The proton affinities of the corresponding phenoxide ions (X-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 22 publications
14
114
1
2
Order By: Relevance
“…Total enthalpies of the studied species X, H(X), at the temperature T are usually estimated from the expression (4) 8,45 H(X) = E 0 + ZPE + ΔH trans + ΔH rot + ΔH vib + RT (4) where E 0 is the calculated total electronic energy, ZPE stands for zero-point energy, ΔH trans , ΔH rot , and ΔH vib are the translational, rotational, and vibrational contributions to the enthalpy, respectively. Finally, RT represents PV-work term and is added to convert the energy to enthalpy.…”
Section: Resultsmentioning
confidence: 99%
“…Total enthalpies of the studied species X, H(X), at the temperature T are usually estimated from the expression (4) 8,45 H(X) = E 0 + ZPE + ΔH trans + ΔH rot + ΔH vib + RT (4) where E 0 is the calculated total electronic energy, ZPE stands for zero-point energy, ΔH trans , ΔH rot , and ΔH vib are the translational, rotational, and vibrational contributions to the enthalpy, respectively. Finally, RT represents PV-work term and is added to convert the energy to enthalpy.…”
Section: Resultsmentioning
confidence: 99%
“…39,42,83,93 DiLabio et al 16,88,95 found that BDE and ΔBDE values of para-substituted phenols, 6-substituted-3-pyridinols, 2-substituted-5-pyrimidinols, and anilines are linearly dependent on Hammett constants σ p . Klein et al 37,48 found that BDE and ΔBDE values of para-substituted and meta-substituted phenols are linearly dependent on Hammett constants σ p and σ m .…”
Section: 36mentioning
confidence: 99%
“…Substituent effects are among the most important concepts of structural effects influencing the chemical, physicochemical, and biochemical properties of chemical species. 35,36 In recent years many previous experimental [22][23][24][37][38][39][40][41][42] and theoretical 12,22,33,[43][44][45][46][47][48][49][50] investigations have been carried out on phenol and mono-substituted phenols in gas and solvent environment. Theoretical study of substituent effect can be utilized in the synthesis of substances with enhanced antioxidant properties.…”
Section: -24mentioning
confidence: 99%
“…In most of the cases the calculated BDE values differ widely from the experimental value. 7 The other methods are more empirically based quantitative structure-activity relationship (QSAR) and quantitative structure-property relationship (QSPR) approaches. In a recent review, 10 quantitative structure-activity relationships have been established for both biological and nonbiological activities and properties of substituted phenols with electronic properties of the substituents.…”
Section: Introductionmentioning
confidence: 99%
“…The rigorous approaches involve quantum mechanical methods including density functional methods, 7 ab initio, 8 and semiempirical methods. 9 The accurate estimation of BDE from theoretical calculations is a challenging task, since high levels of calculations are necessary for taking into account the effect of both the dynamical and the nondynamical part of electron correlation.…”
Section: Introductionmentioning
confidence: 99%